Effect of coffee fermented with bioproduct on seed germination and seedling development - Ferrás Negrín, Yusdel (2021)
IHPLUS is a bioproduct based on efficient microorganisms that constitute an option for the development of cultures. The objective of the research was to evaluate the effect of coffee fermented with IHPLUS on seed germination and posture development. After the pulping of the coffee, the fermentation was carried out in four concentrations with IHPLUS (5%, 10%, 15% and 20%), and a control with water alone. It was evaluated the percentage of germination of the seeds; the height, the length of the root and the dry mass of the seedlings when they had cotyledonous leaves; and the height, the diameter of the stem, the foliar area and the dry mass of the seedlings at the end of their revival. By fermenting the seeds in a medium with a higher concentration of bioproduct, germination was increased, the 15% and 20% treatments increased this indicator by 13,4 and 16,1% respectively compared to the control. In germinators, the seedlings had better morpho-physiological characteristics with the concentrations of the bioproduct, especially with 15%. In the positions, the 15% concentration increased by 17,9; 26,8; 50 and 38,6% height, stem diameter, dry mass and leaf area respectively compared to the control. The IHPLUS in the fermentation of coffee seeds significantly improved the percentage of germination, the quality indicators of the seedlings in the germinators and of the positions at the end of their revival. The 15% concentration was the most comprehensive and recommended variant to use.